Characterization of the Gastric Microbiota in a Pediatric Population According to Helicobacter pylori Status. Issue 2 (February 2017) - Llorca, Laura; Pérez-Pérez, Guillermo; Urruzuno, Pedro; Martinez, Maria Josefa; Iizumi, Tadasu; Gao, Zhan; Sohn, Jiho; Chung, Jennifer; Cox, Laura; Simón-Soro, Aurea; Mira, Alex; Alarcón, Teresa
Abstract : Background: Helicobacter pylori colonizes the human stomach of approximately 50% of the world's population, and increases the risk of several gastric diseases. The goal of this study is to compare the gastric microbiota in pediatric patients with and without H. pylori colonization. Methods: We studied 51 children who underwent gastric endoscopy because of dyspeptic symptoms (18 H. pylori positive and 33 negative). Gastric biopsies were obtained for rapid urease test, culture, histology and DNA extraction. H. pylori was quantified by quantitative polymerase chain reaction and the gastric microbiome studied by V4-16S ribosomal RNA gene high-throughput sequencing. Results: Bacterial richness and diversity of H. pylori -positive specimens were lower than those of negative, and both groups were clearly separated according to beta diversity. Taxonomic analysis confirmed that H. pylori -positive subjects had a higher relative abundance of Helicobacter genus (66.3%) than H. pylori -negative subjects (0.45%). Four phyla (proteobacteria, bacteroidetes, firmicutes and actinobacteria) accounted for >97% of all reads in both groups. Within proteobacteria, gamma- and betaproteobacteria were the most abundant for H. pylori -negative patients, whereas epsilonproteobacteria was for H. pylori positive. H. pylori -positive patients were associated with low body mass index. In the group of underweight patients (body mass index, <18.5), there were 46.1% of H. pylori -positive patients compared with 24% in the nonunderweight group ( P = 0.049). Patients with active superficial gastritis in H. pylori -positive patients had the lowest alpha diversity ( P = 0.035). Conclusions: We characterized the gastric microbiota for the first time in children with and without H. pylori and observed that when H. pylori is present, it tends to dominate the microbial community. In the H. pylori -negative patients, there was more relative abundance of gammaproteobacteria, betaproteobacteria, bacteroidia and clostridia classes and a higher bacterial richness and diversity. Abstract : Supplemental Digital Content is available in the text.